-49=6c-13

Simple and best practice solution for -49=6c-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -49=6c-13 equation:


Simplifying
-49 = 6c + -13

Reorder the terms:
-49 = -13 + 6c

Solving
-49 = -13 + 6c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-6c' to each side of the equation.
-49 + -6c = -13 + 6c + -6c

Combine like terms: 6c + -6c = 0
-49 + -6c = -13 + 0
-49 + -6c = -13

Add '49' to each side of the equation.
-49 + 49 + -6c = -13 + 49

Combine like terms: -49 + 49 = 0
0 + -6c = -13 + 49
-6c = -13 + 49

Combine like terms: -13 + 49 = 36
-6c = 36

Divide each side by '-6'.
c = -6

Simplifying
c = -6

See similar equations:

| 12-7=5-3 | | 3*(x+4)=2*(3-2x) | | 6x+2x+9x=17 | | 4(9n-3)+8n= | | 4x+ab=3 | | 9x*x-6x=1 | | -9(+-2)=-4(+-15) | | X(x+15)-4450=0 | | (-6i)(-6i)(-6i)= | | 3x-3=30x+6 | | 144=-2(7+8x) | | 3(x+10)+4(x+20)+5x=185 | | ab+4x=3 | | z^2=1-i | | (x^2)+10x+17=0 | | 3r^7t^7-6r^8t^6= | | 11x+14y=61979 | | x(9x-6)-1=0 | | 5(q+8)= | | 6(3k-8)=6(k-6) | | x(0.4-0.05x)=0 | | 3m^2-8m-5=0 | | 4x-6+4x=-1+2x | | 5t+16=16-5t | | 2.6+x=6 | | -7(1+5a)=-7(1+6a)-5a | | 20(0.65-4y)+80y=13 | | 59-9=2p+12 | | -6x+8x=46 | | 4(b+8)-2=6b+26 | | 7-14= | | -14+3p+30=14p+28+p |

Equations solver categories